INSERTING LOCAL CULTURES IN BUILDING GOOD CHARACTERS: HOW ARE BOTH CULTURE AND CHARACTER IMPLEMENTED IN A HIGHER EDUCATION CONTEXT? - Ahmad Jamin; Heri Mudra; Suhaimi . (International Conference on Languages and Arts, 2014)
A character building has become the main plan of Kindergarten, Elementary, Junior High, and Senior High Schools. Besides, it is also the main focus in a higher education context such as a college, institute, or university. The character building, in a higher education, has been successfully done by inserting good local cultures as one of influencing factors that affect such character building. The local cultures, including moral values and wisdoms, become predictors of how good characters are formally built. This participatory-observation research studies how such local cultures are implemented in building good characters in a college. The results of this study show that there are at least five ways of inserting such local cultures into the character building, namely: 1) integrating moral values and wisdoms into a lecture preparation (e.g syllabus or teaching materials); 2) being accustomed to implementing local cultures in pre-lecturing, whilst-lecturing, and  post-lecturing activities; 3) integrating such cultures into teaching methods or techniques (e.g think pair share); 4) adjusting such cultures with classroom atmosphere; and 5) combining both culture and character concepts with scientific thoughts.   Keywords: Local cultures, Character Building, Teaching activities, Teaching methods, Scientific thoughts